Penerapan Metode Bercerita dalam Pembelajaran Sirah Nabawiyah: Studi Deskriptif Pada Santri - Mahfudz, Hafidz; Muslimin, Edy (An-Nuha, 2025)
This study aims to examine the application of storytelling methods in the teaching of Sirah Nabawiyah to eleventh-grade students at Pondok Pesantren Al-Atsar 2 Yogyakarta. Utilizing a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings indicate that storytelling methods effectively enhance student engagement and foster a deeper emotional connection to the narratives of the life of the Prophet Muhammad. The students demonstrated a better understanding and greater enthusiasm during the learning process compared to traditional lecture methods. This research also emphasizes the importance of selecting appropriate storytelling techniques and integrating them into lesson planning to optimize the learning experience. Overall, the implementation of storytelling methods presents an effective alternative to enrich religious education, particularly within the context of pesantren. The findings provide practical insights for educators in developing innovative strategies for teaching Islamic history.